IMPLEMENTASI IDZ (INDEKS DESA ZAKAT) PADA MASYARAKAT DESA SELAT BESAR KECAMATAN BILAH HILIR KABUPATEN LABUHAN BATU - I Imsar; K Kamilah; Sinta Pitriyanti (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2021)
The study, entitled Implementation of Zakat Village Index in Selat Besar Village Communities, Bilah Hilir District, Labuhan Batu Regency. This study aims to answer questions about the feasibility of Selat Besar Village, Bilah Hilir District, Labuhan Batu District in receiving zakat funds by BAZNAS. This research uses mixed methods, which is a combination of qualitative and quantitative methods. The analytical tool used is the Zakat Village Index or IDZ with the calculation of the multi-stage weighted index method. This study aims to analyze the Selat Besar village and measure whether it is prioritized to be assisted by zakat funds or not. The results showed that Selat Besar village was categorized as Good with a value of 0.54 and was interpreted to be included in the Fairly Good category, which means that the Village of Selat Besar could be considered to be assisted by BAZNAS with zakat funds.